The RhoGDIβ-Rac1-CARD9 Signaling Module Mediates Islet β-Cell Dysfunction Under Chronic Hyperglycemia - Anjaneyulu Kowluru; Jie-Mei Wang (Cells)
Small (monomeric) GTP-binding proteins (smgs; Cdc42 and Rac1) play requisite roles in islet beta cell function, including glucose-stimulated insulin secretion. In addition, emerging evidence suggests that sustained (constitutive) activation of smgs (e.g., Rac1) culminates in the genesis of islet beta cell dysfunction under the duress of chronic hyperglycemia. It is noteworthy that functions (i.e., activation–deactivation) of smgs in many cells, including the islet beta cell, have been shown to be under the regulatory control of at least three factors, namely the guanine nucleotide exchange factors (GEFs), the GTPase-activating proteins (GAPs), and the GDP-dissociation inhibitors (GDIs). The overall objective of this review is to highlight our current understanding of the regulatory roles of the RhoGDIβ-Rac1-CARD9 signalome in the pathology of beta cell dysfunction under chronic hyperglycemic stress. For brevity, this review is structured by an overview of smgs and their regulatory proteins/factors in the beta cell, followed by a discussion of potential roles of the RhoGDIβ-Rac1-CARD9 axis in the onset of cellular dysfunction under the duress of metabolic stress. Overall conclusions, potential knowledge gaps, and opportunities for future research in this field of islet biology are highlighted in the last section.